Characterization of organic aerosols at the Natura 2000 remote environment of Sanabria Lake (Spain): Evaluating the influence of African dust and regional biomass burning smoke. (1st April 2023) - Pérez-Pastor, Rosa; Salvador, Pedro; García-Gómez, Héctor; García-Alonso, Susana; Toro, Manuel; Artíñano, Begoña; Alonso, Rocío
Abstract: This work presents a thorough analysis of PM10 speciated organic composition at Sanabria Lake Natural Park, a rural remote area in NW-Spain, including diacids, hydroxy and poliacids, fatty acids, alkenoic acids, sugars, sugar alcohols, n-alkanes, PAHs, quinones, hopanes, tracers of biomass burning, and biogenic secondary organic aerosol (BSOA) from isoprene and α-pinene. PM10 ambient concentrations at Sanabria (mean value of 12.2 μg m −3 ) were within the typical range registered in regional-background air quality monitoring stations in Spain. However, the occurrence of African dust outbreaks and biomass burning events produced significant increases in the PM10 levels at this monitoring site (daily mean levels of 29.2 μg m −3 and 13.7 μg m −3, respectively). Major organic compounds were levoglucosan, sacharides and 2-methyltetrols, markers for biomass burning, soil dust and BSOA respectively. SOA contributed more than 53% of the total measured organics in summer Samples with high levels of SOA include most of the African dust events, suggesting that African dust might promote the formation of oxygenated species such as SOA derivatives in this area. This contribution decreased to a 14% in winter. Biomass burning tracers represented 37% of the analysed organic pollutants in winter, indicating that this is the main source of organic compounds in the colder seasons, mainly due to the influence of regional biomass burning events and the use of biomass as fuel in domestic heating. Hence, the fact that African dust outbreaks and biomass burning events are likely to become increasingly frequent in the context of climate change makes this type of analysis particularly relevant for assessing their impact on natural protected areas. Highlights: GC/MS characterization of 76 polar and apolar organic compounds. Natural sources highly contribute to organic aerosol in the background environment. SOA markers predominate in warmer seasons; biomass burning tracers in cold seasons. African dust promote the formation of oxygenated organic compounds. Regional forest fires increase biomass markers and PAH concentrations.